Case Report: Bow Hunter Syndrome—One Reason to Add Non-gravity Dependent Positional Nystagmus Testing to Your Clinical Neuro-Otologic Exam - Schubert, Michael C.; Carter, Nathaniel; Lo, Sheng-fu Larry (Frontiers in Neurology, 2021)
This case study describes transient downbeat nystagmus with vertigo due to a bilateral Bow Hunters Syndrome that was initially treated for seven months as a peripheral benign paroxysmal positional vertigo. Normal static angiography and imaging studies (magnetic resonance, computed tomography) contributed to the mis-diagnosis. However, not until positional testing with the patient in upright (non-gravity dependent) was a transient downbeat nystagmus revealed with vertigo. The patient was referred for neurosurgical consult. Unfortunately, surgery was delayed due to suicidal ideation and hospitalization. Eventually, vertigo symptoms resolved following a C4-5 anterior cervical dissection and fusion (Table 1). This case highlights the critical inclusion of non-gravity dependent position testing as an augment to the positional testing component of the clinical examination as well as the extreme duress that prolonged positional vertigo can cause.